2016
DOI: 10.1095/biolreprod.115.137810
|View full text |Cite
|
Sign up to set email alerts
|

Sialylation Facilitates the Maturation of Mammalian Sperm and Affects Its Survival in Female Uterus1

Abstract: Establishment of adequate levels of sialylation is crucial for sperm survival and function after insemination; however, the mechanism for the addition of the sperm sialome has not been identified. Here, we report evidence for several different mechanisms that contribute to the establishment of the mature sperm sialome. Directly quantifying the source of the nucleotide sugar CMP-beta-N-acetylneuraminic acid in epididymal fluid indicates that transsialylation occurs in the upper epididymis. Western blots for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 36 publications
2
57
0
Order By: Relevance
“…These changes in cervical mucin Sia content may influence sperm Siglec-mediated interactions and transcervical migration. Siglecs, similar to those on B cells (Varki & Angata 2006), may also monitor the Sia population present on the sperm itself, which is known to change at various stages during sperm progression through the female reproductive tract (Ma et al 2016). It is also feasible that Siglecs detecting unique Sia patterns within the female reproductive tract, or on the sperm itself, might exert a regulatory role signalling through their ITAM and ITIM signalling domains as part of their cytoplasmic tail (reviewed in McCauley et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes in cervical mucin Sia content may influence sperm Siglec-mediated interactions and transcervical migration. Siglecs, similar to those on B cells (Varki & Angata 2006), may also monitor the Sia population present on the sperm itself, which is known to change at various stages during sperm progression through the female reproductive tract (Ma et al 2016). It is also feasible that Siglecs detecting unique Sia patterns within the female reproductive tract, or on the sperm itself, might exert a regulatory role signalling through their ITAM and ITIM signalling domains as part of their cytoplasmic tail (reviewed in McCauley et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, in different species, have identified roles for Sia, both on sperm and within the female reproductive tract. Sperm evoke a rapid immune response when deposited within the female reproductive tract (Brandtzaeg 1997, Robertson & Sharkey 2001 and Sia on the sperm surface may facilitate immune tolerance (Toshimori et al 1991, Ma et al 2016. Sperm penetration through cervical mucus is enhanced by mutual repulsion via negatively charged Sia on sperm and mucin glycans (Tollner et al 2008a) and lower levels of sperm negatively charged glycans correlates with subfertility associated with reduced cervical mucus penetration in both the chicken and human (Steele & Wishart 1996, Tollner et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…These glycoproteins inhibit, inter alia, in a sialic acid-dependent way the phagocytosis by leukocytes as seen in murine spermatozoa (30,36). In this regard, the substantial loss of sialic acid residues during epididymitis could prompt phagocytosis of spermatozoa during transit through the epididymis and/or the female reproductive tract, as already indicated (30,37).…”
Section: Discussionmentioning
confidence: 78%
“…We have previously shown that ␣-Neu5Gc antibodies can enter the female reproductive tract in mice and target Neu5Gc-positive sperm (37). Female mice genetically engineered with a human-like Cmah Ϫ/Ϫ mutation and immunized to express ␣-Neu5Gc antibodies show reduced fertility when mated with Neu5Gc-positive wild type males (13,24).…”
mentioning
confidence: 99%
“…Female mice genetically engineered with a human-like Cmah Ϫ/Ϫ mutation and immunized to express ␣-Neu5Gc antibodies show reduced fertility when mated with Neu5Gc-positive wild type males (13,24). Furthermore, human ␣-Neu5Gc antibodies are also capable of targeting paternally derived antigens and can mediate cytotoxicity against Neu5Gc-bearing chimpanzee sperm in vitro (13), (37). Here, we investigate the possible consequences of the presence of Neu5Gc and ␣-Neu5Gc antibodies in the reproductive system in a mouse model humanized for its sialic acid and ␣-xenoglycan immune response.…”
mentioning
confidence: 99%